High-Throughput Analysis of Lidocaine in Pharmaceutical Formulation by Capillary Zone Electrophoresis Using Multiple Injections in a Single Run - Andressa C. Valese; Daniel A. Spudeit; Maressa D. Dolzan; Lizandra C. Bretanha; Luciano Vitali; Gustavo A. Micke (Journal of Analytical Methods in Chemistry)
This paper reports the development of a subminute separation method by capillary zone electrophoresis in an uncoated capillary using multiple injection procedure for the determination of lidocaine in samples of pharmaceutical formulations. The separation was performed in less than a minute leading to doing four injections in a single run. The cathodic electroosmotic flow contributed to reducing the analyses time. The background electrolyte was composed of 20 mmol L−1 2-amino-2-(hydroxymethyl)-1,3-propanediol and 40 mmol L−1 2-(N-morpholino)ethanesulfonic acid at pH 6.1. The internal standard used was benzylamine. Separations were performed in a fused uncoated silica capillary (32 cm total length, 23.5 cm effective length, and 50 μm internal diameter) with direct UV detection at 200 nm. Samples and standards were injected hydrodynamically using 40 mbar/3 s interspersed with spacer electrolyte using 40 mbar/7 s. The electrophoretic system was operated under constant voltage of 30 kV with positive polarity on the injection side. The evaluation of some analytical parameters of the method showed good linearity (r2>0.999), a limit of detection 0.92 mg L−1, intermediate precision better than 3.2% (peak area), and recovery in the range of 92–102%.